Unilateral Optic Nerve Aplasia (ONA) in an otherwise Healthy Child: A Case Report and Literature Review - HASHEM S. ALMARZOUKI; OMAR A. ROZY; WALEED M. ALKHURAIMI; MUSAB A. ALSUBAIE (International Journal of Pharma and Bio Sciences, 2018)
Optic nerve aplasia (ONA) is a rare congenital anomaly characterized by the absence of the optic nerve, central retinal vessels and retinal ganglion cells. Unilateral ONA is generally associated with otherwise normal brain development, while bilateral ONA usually has other central nervous system malformation. ONA occurs sporadically without sexual or racial predilection. The diagnosis of ONA requires a complete ophthalmic examination and the help of neuroimaging. An updated literature review demonstrated that 38 cases were reported from 1977 to 2012. This case report, presents an 18-month-old preterm female baby who shows the characteristic findings of ONA in contrast to numerous reports that misidentified aplasia. In addition, this unilateral ONA has the extremely unique finding of a normal sized eye, in contrast to the majority of reported cases that have microphthalmos.